1996
DOI: 10.1080/15513819609168699
|View full text |Cite
|
Sign up to set email alerts
|

Extralobar Sequestration and Type II Congenital Cystic Adenomatoid Malformation in an Infant with Congenital Diaphragmatic Hernia

Abstract: This case report describes an infra-diaphragmatic sequestrated type II congenital cystic adenomatoid malformation (CCAM) containing striated muscle fibers in the stroma occurring in association with an extra-lobar sequestration (ELS) and a congenital diaphragmatic hernia in a female neonate. The classification and pathogenesis of CCAM and ELS are reviewed and the relationships between these lesions discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Other studies have reported associations of pulmonary sequestrations and CPAM with congenital diaphragmatic hernias and bronchogenic cysts [ 7 ]. The coexistence of separate anomalies in one lesion suggests that they are ends of a spectrum, rather than separate entities, and it has been suggested that it is more logical to describe all congenital cystic lung lesions as “congenital thoracic malformations” [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported associations of pulmonary sequestrations and CPAM with congenital diaphragmatic hernias and bronchogenic cysts [ 7 ]. The coexistence of separate anomalies in one lesion suggests that they are ends of a spectrum, rather than separate entities, and it has been suggested that it is more logical to describe all congenital cystic lung lesions as “congenital thoracic malformations” [ 8 ].…”
Section: Discussionmentioning
confidence: 99%